Masticatory muscle activity in complete denture wearers: a surface electromyographic analysis - Nazia Rasheed; Suja Joseph; Aby Mathew T; Veena Paul; Shibi Mathew; Joshy ` Abraham (Indonesian Journal of Prosthodontic, 2022)
The investigation of the adaptation process to a new denture is relevant to understand the control of muscles. Surface electromyography provide reproducible data of masticatory muscle function and helps to assess the performance of dentures. This longitudinal study simultaneously evaluated electric potential in masseter and anterior temporalis during clenching at maximum intercuspation position and mastication at 2 months after denture insertion and one year later was done in complete denture patients. The surface electrodes were placed in anterior temporalis and ma-sseter region of 22 patients during maximum voluntary clenching and chewing. Statistical analysis was performed by paired t-test. A significant increase in electrical activity was found during clenching and chewing after one year compared to two months. The overall mean EMG value of masseter was significantly higher during chewing at 2 months (p<0.001) and 1 year (p<0.001). A negative correlation was found with respect to age and EMG value of ma-sseter. It is concluded that the electrical activity presented statistically significant difference after one year indicating improved functional quality. A good rehabilitation improves the efficiency of muscles. Monitoring the effect of rehabili-tation on stomatognathic system help to preventively warn about dysfunctions and treatment modifications needed.